(untitled) (Communications in Mathematical Research, 2020)
The first part of this article is an overview on some recent major developments in the field of analysis and partial different equations. It is a brief presentation given by the author at a round table discussion. The second part is a supplement of various details provided by several outstanding researchers on subjects.